2014
DOI: 10.1007/s10902-014-9542-3
|View full text |Cite
|
Sign up to set email alerts
|

Using a Gratitude Intervention to Enhance Well-Being in Older Adults

Abstract: The increasingly ageing population includes a proportion of well older adults that may benefit from low-level psychological support to help maintain their wellbeing. A factor consistently regarded as integral to wellbeing is gratitude. The effect of a 'Three good things in life' gratitude intervention on hedonic and eudemonic wellbeing and perceived stress levels in non-clinically depressed older adults was examined. This intervention has not been evaluated with older adults previously. The duration of the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
0
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(129 citation statements)
references
References 55 publications
5
103
0
12
Order By: Relevance
“…Problem-focussed coping skills can be developed via training courses. Gratitude, hope, and self-efficacy are character strengths that can also be developed using positive psychology interventions (Emmons & McCullough, 2003;Killen & Macaskill, 2014). This then provides new approaches to stress management training to augment the more traditional approaches.…”
Section: Summary and Implicationsmentioning
confidence: 99%
“…Problem-focussed coping skills can be developed via training courses. Gratitude, hope, and self-efficacy are character strengths that can also be developed using positive psychology interventions (Emmons & McCullough, 2003;Killen & Macaskill, 2014). This then provides new approaches to stress management training to augment the more traditional approaches.…”
Section: Summary and Implicationsmentioning
confidence: 99%
“…Since the publication of Seligman and Csikszentmihaly's article, the number of PPIs studies has increased rapidly worldwide, it appears that PPIs are effective in enhancing wellbeing. Many of these studies demonstrated the efficacy of PPIs on well-being such as gratitude (Killen and Macaskill 2014), forgiveness (Reed and Enright 2006), life review therapy (Preschl et al 2012), positive reminiscence (Meléndez Moral et al 2014) and self-management (Frieswijk et al 2006). There are four factors that appear to enhance the effectiveness of PPIs:…”
Section: Positive Psychological Interventions (Ppis)mentioning
confidence: 99%
“…Four studies included follow-up measures with the varied time scales, two completing the follow up after 1 month (Killen and Macaskill 2014;Chiang et al 2008), one at 3 months (Preschl et al 2012), and one at 6 months (Frieswijk et al 2006). Due to the variations in the well-being measures utilized, the study designs (including only four RCTs), intervention content and behaviours targeted, it was not possible to conduct a thorough meta-analysis on the data.…”
Section: General Selected Study Characteristicsmentioning
confidence: 99%
“…A 2012 study found that writing letters of gratitude, instead of keeping a journal or diary, increased happiness and life satisfaction and decreased depressive symptoms in the experimental group when compared to the control group (Toepfer, Cichy, & Peters, 2012). Another recent study found that an online gratitude intervention increased eudemonic well-being (feeling like life is meaningful, rather than simply pleasurable (Hui, Glitza, Chisholm, Yennu, & Bruera, 2013)) and decreased stress in a sample of 88 healthy, communitydwelling older adults when compared to controls, and no difference was found between the electronic gratitude journal and a paper version (Killen & Macaskill, 2014).…”
Section: Manipulations Of Gratitudementioning
confidence: 97%
“…The prompt will focus on the experience of the emotion rather than the length or completeness of the writing itself. These instructions are consistent with other gratitude interventions that have been successfully studied (Emmons, 2010;Emmons & McCullough, 2003a;Kerr et al, 2014;Killen & Macaskill, 2014;Ruini & Vescovelli, 2013). The full prompt is included in Appendix C.…”
Section: Interventionmentioning
confidence: 97%